Sleep Quality in Patients with Tinnitus - Unchalo, Adriana Laybauer Silveira; Santos, Cauê Denardi; Weingaertner, Laura Weber; Selaimen, Fábio André; Sartor, Nicole Cislaghi; Teixeira, Adriane Ribeiro (Sleep Science, 2025)
To analyze the association between sleep quality and chronic tinnitus.The present is a prospective observational cross-sectional study in which convenience sampling (n = 51) was used to assess individuals with chronic tinnitus at a specialized outpatient clinic in a tertiary referral hospital. The data collection tools included a demographics questionnaire, a sleep quality questionnaire (the Mini Sleep Questionnaire), a questionnaire to assess the impact of tinnitus (Tinnitus Handicap Inventory), and pure-tone audiometry. The data was analyzed using the student's t-test or analysis of variance (ANOVA), the Mann-Whitney or Kruskal-Wallis's test, and the Pearson's Chi-squared or Fisher's exact test.There was a predominance of women and middle-aged adults with bilateral tinnitus and hearing loss. The scores on the Tinnitus Handicap Inventory revealed that the tinnitus had a moderate to catastrophic impact on quality of life. Most participants classified themselves as having severe sleep difficulties on the Mini Sleep Questionnaire. Furthermore, patients with higher scores on the Tinnitus Handicap Inventory tended to show poor quality sleep patterns on the Mini Sleep Questionnaire. Regarding the association between sex and the scores on the Tinnitus Handicap Inventory, more men were severely handicapped, whereas more women were catastrophically handicapped. There was also a significant association between age group and hearing loss.The data analysis revealed a significant association between sleep quality and tinnitus in the sample.
Keywords: tinnitus; sleep quality; quality of life